Seed production of vegetables is lucurative horti-business - Singh, P M; Singh, P K; Manimurugan, C; Kumar, Rajesh; Singh, Rameshwar; Singh, B (Indian Horticulture, 2015)
The vegetable seed production could be an important horti-business, contributing not only for the welfare of growers/entrepreneurs but for the country as a whole by bridging the gap between demand and supply of quality vegetable seed.